Outage capacity of rate-adaptive relaying for FSO links with nonzero boresight pointing errors - Boluda-Ruiz, Rubén; García-Zambrana, Antonio; Castillo-Vázquez, Beatriz; Castillo-Vázquez, Carmen; Qaraqe, Khalid; qaraqe (Institute of Electrical and Electronics Engineers, 2019)
An outage capacity analysis of a three-way free-space optical (FSO) setup based on the optical path selection, either source-destination (S-D) or source-relay-destination (S-R-D), with a greater value of channel gain along with the use of repetition coding (RC) is analyzed over atmospheric turbulence channels with nonzero boresight pointing errors. The developed expression, which is validated through Monte Carlo simulation, is used to carefully analyze the performance and design of rate-adaptive relaying FSO systems from an information theory point of view. It is highlighted that a greater outage diversity is achieved by the obtained results without investing in extra hardware at the expense of an information rate reduction.
This is the accepted manuscript (postprint) of the article published in IEEE Photonics Technology Letters. The final published version is available at https://doi.org/10.1109/LPT.2019.2906578.
Keywords: Fotónica; Optoelectrónica; Atmospheric modeling; Adaptive optics; Optical fiber communication; Receivers; Optical transmitters; Signal to noise ratio; Relays; FSO; Outage capacity; Atmospheric turbulence